2001
DOI: 10.1128/iai.69.1.613-616.2001
|View full text |Cite
|
Sign up to set email alerts
|

Differential Interleukin-8 Response of Intestinal Epithelial Cell Line to Reactogenic and Nonreactogenic Candidate Vaccine Strains of Vibrio cholerae

Abstract: In this study, we analyzed whether attachment of Vibrio cholerae vaccine strains to human intestinal epithelial cells can induce an interleukin-8 (IL-8) response. The IL-8 transcripts were detected by PCR amplification of reverse-transcribed mRNA, and the gene product secretion was measured by an enzyme-linked immunosorbent assay. Infection of monolayers of the undifferentiated HT29-18N2 cell line with reactogenic (JBK70 and 81) and nonreactogenic (CVD103HgR and 638) vaccine strains of V. cholerae resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 24 publications
7
33
2
Order By: Relevance
“…5). This observation is consistent with the findings of a separate study, which demonstrated that strain CVD103-HgR induced less transcription and synthesis of IL-8 than other attenuated strains of V. cholerae in another intestinal epithelial cell line (47). These findings correlate with volunteer studies with these two classical strains, which found CVD101 to be reactogenic, while CVD103-HgR was nonreactogenic.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…5). This observation is consistent with the findings of a separate study, which demonstrated that strain CVD103-HgR induced less transcription and synthesis of IL-8 than other attenuated strains of V. cholerae in another intestinal epithelial cell line (47). These findings correlate with volunteer studies with these two classical strains, which found CVD101 to be reactogenic, while CVD103-HgR was nonreactogenic.…”
Section: Discussionsupporting
confidence: 91%
“…For example, CVD101 activated greater expression of the genes for IL-8 and MIP-3␣ than CVD103-HgR (Table 2). These results are consistent with previous studies that have shown CVD103-HgR to be nonreactogenic and well tolerated in human volunteers (30) and also to induce less IL-8 expression in the intestinal epithelial cell line HT29-18N2 (47). The nonreactogenic nature of CVD103-HgR may be due to it being derived from a strain (569B) with reduced ability to colonize the intestine (30).…”
Section: Effects Of V Cholerae Infection On Global Gene Expression Psupporting
confidence: 91%
See 1 more Smart Citation
“…The hap gene is positively regulated by HapR at the transcription level (20). It was reported that a CTX and hap-defective vaccine strain, 638, was not reactogenic in human volunteers and this strain induced lower levels of IL-8 than its parent wild-type strain in HT29 cells (38). The protease activity in V. cholerae vaccine strains has been associated with decreases in the transcellular epithelial resistance of polarized T84 intestinal epithelial cells (31).…”
mentioning
confidence: 99%
“…The inflammatory response to V. cholerae is characterized by neutrophil infiltration in the intestinal epithelium and the underlying lamina propria [7]. We and others previously demonstrated elicitation of IL-8 in epithelial cells exposed to V. cholerae laboratory as well as vaccine strains [13,14]. A number of attempts have been made to identify the V. cholerae components contributing to IL-8 expression.…”
Section: Introductionmentioning
confidence: 99%